TA Treatment of Emetophobia - A Hermeneutic Single-Case Efficacy Design Study – ‘Peter’ - Colin Kerr (International Journal of Transactional Analysis Research, 2013)
This study reports on theapplication of Hermeneutic Single Case Efficacy Design (HSCED) (Elliott 2002) to a 39 session TA-based psychotherapy intervention with a 19 year old white male student in the UK who was suffering from emetophobia. The author, who was also the researcher, provides literature reviews on emetophobia clinical characteristics,contrasts it with other phobias, and reviews prior research including TA-based approaches to phobias generally. HSCED Methodology is briefly described; quantitative outcome measures are obtained and analysed using GAD-7 (Spritzer et al 2006)and SPQ (Elliott et al 1999), and qualitative measures via a rich case record, session recordings/transcripts, and a 4-month follow-up interview.  Bohart at al’s (2011) 56 criteria for evidence adjudication were used alongside HSCED criteria. There was strong evidence of significant client changes, and that these changes were the result of the therapy.